Larrea divaricata Cav. aqueous extract and nordihydroguariaretic acid modulate oxidative stress in submandibular glands of diabetic rats : a buccal protective in diabetes - Peralta, Ignacio (2019)
Fil: Peralta, Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina